IgG anti-RBD levels during 8-month follow-up post-vaccination with BNT162b2 and mRNA-1273 vaccines in healthcare workers: A one-center study - Gil-Manso, Sergio; Alonso, Roberto; Catalán, Pilar; Sánchez-Arcilla, Ignacio; Marzola, Marco; Correa-Rocha, Rafael; Pion, Marjorie; Muñoz, Patricia; , Gregorio Marañón Microbiology-ID COVID-19 Study Group; Alcalá, Luis; Aldámiz, Teresa; Alonso, Roberto; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Since the COVID-19 outbreak, specific mRNA-based anti-SARS-CoV-2 vaccines have been developed and distributed worldwide. Because this is the first time that mRNA vaccines have been used, there are several questions regarding their capacity to confer immunity and the durability of the specific anti-SARS-CoV-2 response. Therefore, the objective of this study was to recruit a large cohort of healthcare workers from the Gregorio Marañón Hospital vaccinated with the mRNA-1273 or BNT126b2 vaccines and to follow-up on IgG anti-RBD levels at 8 months post-vaccination. Methods We recruited 4,970 volunteers and measured IgG anti-RBD antibodies on days 30 and 240 post-vaccination. Results We observed that both vaccines induced high levels of antibodies on day 30, while a drastic wane was observed on day 240, where mRNA-1273 vaccinated induced higher levels than BNT162b2. Stratifying by vaccine type, age, gender, and comorbidities, we identified that older mRNA-1273-vaccinated volunteers had higher antibody levels than the younger volunteers, contrary to what was observed in the BNT162b2-vaccinated volunteers. Discussion In conclusion, we observed that mRNA-1273 has a higher capacity to induce a humoral response than BNT162b2 and that age is a factor in the specific response.